A process for developing standards to promote quality in general practice. (2nd June 2018) - Khoury, Julie; Krejany, Catherine J; Versteeg, Roald W; Lodewyckx, Michaela A; Pike, Simone R; Civil, Michael S; Jiwa, Moyez
Abstract: Background: Since 1991, the Royal Australian College of General Practitioners' (RACGP) Standards for General Practices (the Standards) have provided a framework for quality care, risk management and best practice in the operation of Australian general practices. The Standards are also linked to incentives for general practice remuneration. These Standards were revised in 2017. Objective: The objective of this study is to describe the process undertaken to develop the fifth edition Standards published in 2017 to inform future standards development both nationally and internationally. Method: A modified Delphi process was deployed to develop the fifth edition Standards. Development was directed by the RACGP and led by an expert panel of GPs and representatives of stakeholder groups who were assisted and facilitated by a team from RACGP. Each draft was released for stakeholder feedback and tested twice before the final version was submitted for approval by the RACGP board. Results: Four rounds of consultation and two rounds of piloting were carried out over 32 months. The Standards were redrafted after each round. One hundred and fifty-two individuals and 225 stakeholder groups participated in the development of the Standards. Twenty-three new indicators were recommended and grouped into three sections in a new modular structure that was different from the previous edition. Conclusion: The Standards represent the consensus view of national stakeholders on the indicators of quality and safety in Australian general practice and primary care.